2014
DOI: 10.1523/jneurosci.0855-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19b Associates with Ago2 in the Amygdala Following Chronic Stress and Regulates the Adrenergic Receptor Beta 1

Abstract: Activation of the stress response in the presence of diverse challenges requires numerous adaptive molecular and cellular changes. To identify specific microRNA molecules that are altered following chronic stress, mice were subjected to the chronic social defeat procedure. The amygdala from these mice was collected and a screen for microRNAs that were recruited to the RNA-induced silencing complex and differentially expressed between the stressed and unstressed mice was conducted. One of the microRNAs that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…MiR-34c reduced the responsiveness of cells to CRF in neuronal cells endogenously expressing CRFR1. In basolateral amygdala of mice, Volk et al (2014) recently showed that miR-19b is modulated in response to social-defeat stress, which was associated with altered expression of adrenergic receptor β-1. Bilaterally injection with miR-19b into the this brain area showed lower freezing time relative to control in the cue fear conditioning test, and caused deregulation of noradrenergic circuits mediated through adrenergic receptor β-1.…”
Section: Regulation Of Mirnas By Stress: Possible Implications In Depmentioning
confidence: 99%
“…MiR-34c reduced the responsiveness of cells to CRF in neuronal cells endogenously expressing CRFR1. In basolateral amygdala of mice, Volk et al (2014) recently showed that miR-19b is modulated in response to social-defeat stress, which was associated with altered expression of adrenergic receptor β-1. Bilaterally injection with miR-19b into the this brain area showed lower freezing time relative to control in the cue fear conditioning test, and caused deregulation of noradrenergic circuits mediated through adrenergic receptor β-1.…”
Section: Regulation Of Mirnas By Stress: Possible Implications In Depmentioning
confidence: 99%
“…Recent studies have linked microRNA (miRNA) expression or biogenesis dysregulation to various psychiatric disorders, including anxiety and depression (Dias et al., 2014b, Issler and Chen, 2015, Issler et al., 2014, Lopez et al., 2014, O’Connor et al., 2012, Volk et al., 2014). However, changes in miRNA expression levels do not necessarily reflect their immediate activity; it is only when a specific miRNA, in the canonical pathway, has matured and been incorporated into the RNA-induced silencing complex (RISC) in the presence of argonaute RISC catalytic component 2 (Ago2) that it becomes truly active (Meister et al., 2004) as a result of its association with its target mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…miR-34c is involved in regulating stress-induced anxiety (Haramati et al., 2011) and miR-34a in fear memory consolidation (Dias et al., 2014a). Furthermore, miR-19b plays an important role in memory consolidation following stress by regulating the adrenergic receptor beta 1 (Volk et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a precursor miRNA family, mir-19b, has been implicated in PTSD [20,21] and is differentially expressed between SS and SR mice in our own laboratory. This same miRNA is enhanced in the amygdala following chronic social defeat stress and mir-19b in vivo manipulation bidirectionally modulated cued fear conditioning without altering contextual fear memory or anxiety-like behavior in the OFT, dark/light transfer test, or the EPM [14]. Further study of miRNAs altered by stress, such as mir-19b or mir-598-3p, which specifically influence amygdala-dependent memory without altering general anxiety-like behavior, may provide further insight into mechanisms contributing to PTSD.…”
Section: Discussionmentioning
confidence: 87%
“…We have previously shown that cued fear conditioning downregulates miR-182 in the lateral amygdala and that overexpression of miR-182 in this region during training disrupted expression of the fear memory the following day [12]. While these reports and others provide evidence that miRNAs can influence memory formation [13][14][15], studies to date have not addressed their impact on remote memory.…”
Section: Introductionmentioning
confidence: 99%